The genetic landscape of childhood-onset dystonia in a nationwide Turkish cohort: Clinical spectrum, molecular diagnostics, and therapeutic implications - Yilmaz, Sanem; Serdaroglu, Esra; Simsek, Erdem; Kara, Bulent; Turkdogan, Dilsad; Yis, Uluc; Tekgul, Hasan (Elsevier Sci Ltd, 2026)
Background: Childhood-onset dystonia (COD) encompasses a clinically and etiologically heterogeneous group of disorders, often with overlapping features. Genetic testing plays a pivotal role in uncovering underlying causes, identifying treatable subtypes, and informing individualized management strategies. Objective: To delineate the molecular genetic etiology, phenotypic characteristics, and treatment strategies in a multicenter cohort with gene-related CODs. Methods: The study cohort comprised 81 patients with gene-related COD from 19 tertiary pediatric neurology centers in Turkiye. Clinical phenomenology, biochemical, electrophysiological, neuroimaging findings, diagnostic genetic tests, causative genes and variants, inheritance patterns, gene-related phenotypes, treatment modalities, and their efficacy were gathered. Results: A diverse genetic landscape was identified in the cohort of 81 patients, revealing 62 distinct (pathogenic/ likely pathogenic) variants across 26 genes. The genetic diagnoses were established through whole-exome sequencing (49.4%), single-gene testing (25.9%), and targeted gene panels (23.5%). Of the 81 patients, 59 had single-nucleotide variants (SNVs), 21 had deletions or duplications, and one patient carried a pathogenic trinucleotide repeat expansion. The common etiologies of gene-related COD were KMT2B (16%), GCH1 (11.1%), SLC2A1 (11.1%), GNAO1 (8.6%), TOR1A (8.6%), GNAL (6.2%). Rare etiologies were SLC18A2 and TH (each 4.9%), ATP1A3, NKX2-1, PRKN, SCN4A, THAP1 (each 2.5%), and ultra-rare etiologies (single patients) were: ACY5, ADPRS, ANO3, COL6A3, DNM1L, GNB1, HTT, PRKRA, PRRT2, RHOBTB2, SETX, SLC6A3, TUBB4A (1.2%). Based on Gene Ontology classification, the most represented functional categories were neurotransmission (n = 18, 22.2%), gene expression (n = 17, 20.9%), and signaling (n = 14, 17.3%). Genetic diagnosis influenced treatment modalities with pharmacotherapy modification or implementation of deep brain stimulation in 60.5% of the cohort, with targeted therapies being more effective than symptomatic treatments (p = 0.0118). Conclusion: This nationwide study highlights the phenotypic and genetic diversity of gene-related COD with certain therapeutic implications based on the molecular etiology-specific diagnosis.
Keywords: Childhood; Dystonia; Genetic; Hyperkinetic; Movement Disorder